Arabic Language Online Learning System - Omar, Ei Shibani Mohamed R. (2008)
In recent times, there has been a strong push for higher education institutions to offer more online courses to cater for students who otherwise would be denied university education. While this may benefit the many distance education students, the take-up rate of totally online education by current on-campus students remains uncertain. At the same time, many lecturers have started to design and develop online teaching material for their courses; many do so without the support of their employer which is the university that they work in. The purpose of this study is two-fold. Firstly, to gain an insight into how UUM's (Universiti Utara Malaysia) students perceive online Arabic learning and to examine their readiness and willingness to make the shift from conventional classroom learning to online learning with no face-to-face contact. Secondly, to develop an online learning system for teaching Arabic language so that teaching can be made more effective and at the same time enjoyable. Students can learn Arabic language via the online system anytime, anywhere and at anyplace.